Calcium-permeable ion channels in control of autophagy and cancer - Kondratskyi, Artem; Yassine, Maya; Kondratska, Kateryna; Skryma, Roman; Slomianny, Christian; Prevarskaya, Natalia (Frontiers in Physiology, 2013)
Autophagy, or cellular self-eating, is a tightly regulated cellular pathway the main purpose of which is lysosomal degradation and subsequent recycling of cytoplasmic material to maintain normal cellular homeostasis. Defects in autophagy are linked to a variety of pathological states, including cancer. Cancer is the disease associated with abnormal tissue growth following an alteration in such fundamental cellular processes as apoptosis, proliferation, differentiation, migration and autophagy. The role of autophagy in cancer is complex, as it can promote both tumor prevention and survival/treatment resistance. It’s now clear, that modulation of autophagy has a great potential in cancer diagnosis and treatment. Recent findings identified intracellular calcium as an important regulator of both basal and induced autophagy. Calcium is a ubiquitous secondary messenger which regulates plethora of physiological and pathological processes such as aging, neurodegeneration and cancer. The role of calcium and calcium-permeable channels in cancer is well established, whereas the information about molecular nature of channels regulating autophagy and the mechanisms of this regulation is still limited. Here we review existing mechanisms of autophagy regulation by calcium and calcium-permeable ion channels. Furthermore, we will also discuss some calcium-permeable channels as the potential new candidates for autophagy regulation. Finally we will propose the possible link between calcium permeable channels, autophagy and cancer progression and therapeutic response.